Young adults’ personal views on child abuse - Carolina Anne Jernbro; Ulla-Britt Eriksson; Staffan Janson (Nordic Journal of Social Research)
This is a qualitative study based on reports from young adults, both exposed and not exposed to child abuse. The aim of the present study has been to analyse young adults' thoughts and feelings about child abuse. The data consisted of 358 responses to an open-ended question included in a national postal questionnaire study carried out by the Swedish Committee Against Child Abuse (Kommittén mot barnmisshandel). The analysis of data involved qualitative content analysis. Four main categories emerged: children's rights, consequences of child abuse, the role of the society, and causes of child abuse. The respondents who were abused as children wrote about the experience and the psychological long-term consequences of the abuse. The psychological abuse was particularly detrimental. The sexually abused expressed feelings of shame and guilt, in particular the young men. The non-abused respondents reported primarily on more general issues. They expressed children's right to a safe childhood and they strongly believed in stricter penalties for child abusers.